Profile of Skin Diseases in The Ederley at Nursing House Surakarta - Mawardi, Prasetyadi; Oktavriana, Triasari; Murastami, Ammarilis; Murasmita, Alamanda; Pradestine, Sesia; Esa Putri, Osdatilla Esa; Lidjaja, Lifesia Natali; Alia, Vrenda; Kusumasari, Nila (Universitas Baiturrahmah, 2025)
Background: The elderly population has been rapidly increasing over the past few decades. In Indonesia, the percentage of elderly residents is 8.75% of the total population. Aging is an unavoidable process, but it requires care to ensure a good quality of life for the elderly. One of the issues affecting the quality of life in the elderly is skin aging. Skin aging causes various complaints, especially itching or pruritus, which can reduce the quality of life for the elderly. Knowledge of the pathophysiology of skin diseases and skin aging, as well as the factors that affect them, particularly skin hydration, is necessary. This research is expected to be beneficial for medical professionals as well as family members of the elderly. The elderly residents at Wreda Griya PMI Peduli and Aisyiyah Nursing Home come from various regions and economic backgrounds. Therefore, the researchers consider the nursing home to be an appropriate place to conduct this study, as it can represent the elderly population from diverse backgrounds across Indonesia.Objective: This study aims to analyze the various skin disease profiles at the Griya PMI Peduli and Aisyiyah nursing homes in the city of Surakarta. Methods: This type of research is a survey using an observational study method with a descriptive design. Results: There were a total of 45 subjects at the Wreda PMI Peduli and Aisyiyah Nursing Home in Surakarta. Among them, 34 subjects had skin complaints, while 11 subjects were excluded because they did not have any skin complaints (7 subjects) or were uncooperative (4 subjects). The most common diagnosis was xerosis cutis (53%). The majority of patients did not have comorbidities (65%), with the most common comorbidity being hypertension (26%). Conclusion: The results of this study indicate that all the main skin complaints among the elderly at Panti Wreda in Kota Surakarta were dominated by itching or pruritus, with xerosis cutis being the primary etiology of pruritus in the elderly subjects of the study, accounting for 53%.